A watermarking scheme for relational databases with categorical data - Hương, Lưu Bích; Hồng, Bùi Thế (Journal of Computer Science and Cybernetics, 2013)
Watermarking is one of the effective measures for copyright protection and the integrity of the relational database in the Internet environment. In this paper, we propose a new watermarking scheme which can detect and localize the tampering of the relational database with categorical data. This watermarking scheme does not change any value in the database, but only changes secretly and securely the order of the tuples in the database.